(untitled) (Third Sector Social Economic Review, 2023)
Countries’ opening their borders to free trade has brought with it increased competition conditions with globalization. The increase in the trade potential has been the most important issue for countries. For this purpose, international and regional trade organizations have been established, thus it has aimed facilitating and developing international trade. Due to its strategic position in Turkey, it has important opportunities to improve its international trade volume. In this context, the paper aims to determine the countries of the Shanghai Cooperation Organization, which are potential export markets by analyzing Turkey’s export potential to Shanghai Cooperation Organization member countries. Apart from Iran whose data can not be accessed, the annual data of China, Russia, India, Kyrgyzstan, Tajikistan, Kazakhstan, Uzbekistan and Pakistan are included in the analysis between the years 2000-2020. As a result of the paper, it is observed that actual exports of Turkey are more than its export potential to Tajikistan, Kyrgyzstan, Uzbekistan, Pakistan and India, while it is determined that actual exports to Russia are at a level close to its export potential. In addition, it has been determined that the actual exports to China and Kazakhstan are below the export potential and these two countries are important target export markets among the Shanghai Cooperation Organization member countries.